Pesticide Safety Miniposter IPM: Beyond Spraying - R.W. Baldwin; S.K. Hill; Phillip Koehler; J.C. Medley; P.A. Mitola (EDIS)
Pest management involves more than just spraying pesticides. It includes diagnosing the pest situation and developing a comprehensive plan. This educational poster is designed to acquaint new pest control technicians with the steps in IPM. Published August 2012.